1992
DOI: 10.1288/00005537-199206000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sequelae of intraparenchymal bismuth subgallate

Abstract: Bismuth subgallate (BSG) is a heavy metal compound which is effective in lowering the incidence of hemorrhage after adenotonsillectomy and has been demonstrated to activate Factor XII. In a minority of children, the paste has been suctioned from the cuffless oral endotracheal tube after adenotonsillectomy. No pulmonary sequelae have been noted in these patients. To assess the effect of BSG aspiration, 75 rats were divided into groups receiving either intratracheal BSG or saline. Early and late parenchymal effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…A miliary granulomatous reaction may be seen with the aspiration of medications like cholestyramine, phenobarbital and phenytoin [16]. A giant cell foreign-body reaction is seen in rats following experimental aspiration of bismuth subgallate [17], peptobismol and kaopectate [18]. Two cases with respiratory failure following activated charcoal aspiration in adults have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A miliary granulomatous reaction may be seen with the aspiration of medications like cholestyramine, phenobarbital and phenytoin [16]. A giant cell foreign-body reaction is seen in rats following experimental aspiration of bismuth subgallate [17], peptobismol and kaopectate [18]. Two cases with respiratory failure following activated charcoal aspiration in adults have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, investigations in animals indicate that aspiration to the lungs results in acute pneumonia followed by a foreign‐body response. 12 The risk of electrocautery‐induced ignition of the swabs by using diathermy is increased if BSG is used. 13 In addition, BSG paste has a tendency to smudge the operation field.…”
Section: Discussionmentioning
confidence: 99%
“…We X-rayed 30 patients post-operatively and found no evidence of pharyngeal opacities. A recent study by Cozzi et al (1991) where they injected rats intratracheally with bismuth subgallate paste found that it caused pneumonia in a significant number of them. There were no laryngeal or respiratory complications in any of our patients but it still must be kept in mind that there is a theoretical risk of respiratory problems when using this paste.…”
Section: Discussionmentioning
confidence: 99%